Makna Moderasi dalam Ritual Ngareremokeun Masyarakat Kasepuhan Cisungsang, Lebak-Banten - Mahmudah Nur; Novita Siswayanti; Nurrahmah Nurrahmah (Jurnal SMART (Studi Masyarakat, Religi, dan Tradisi), 2021)
The Ngareremokeun ritual is a form of indigenous community belief in the Kasepuhan Cisungsang who live around the Mount Halimun Salak National Park (TNGHS) Lebak Regency, Banten Province toward customary law as the embodiment of ancestral mandates. The Ngareremokeun tradition is also evidence of various cultures acculturation without eliminating another cultural element. This paper aims to understand the meaning of moderation as reflected in the Ngareremokeun ritual and to show its relevance to the context of the community that owns the tradition and Indonesian society in general. This descriptive study emphasizes on qualitative data with a structuralist approach that aims to describe the moderation values reflected in the Ngareremokeun ritual. Data was collected through interviews with cultural actors and direct observation on the Ngareremokeun ritual. The results of this study indicate that the Ngareremokeun ritual is the evidence of knowledge resource and cultural expression of indigenous people in the Kasepuhan Cisungsang to maintain the sustainability of their traditions. The meaning of the symbols embodied in this tradition, the moderation values in the Ngareremokeun ritual is appropriate with the four indicators of religious moderation, namely national commitment, tolerance, non-violence, and accommodating to local culture. The moderation value can also be found in the attitudes and behavior of the Ngararemokeun’s actors and the indigenous people in Kasepuhan Cisungsang.